2001
DOI: 10.1007/s002640100259
|View full text |Cite
|
Sign up to set email alerts
|

Operative treatment of progressive deformity in spinal tuberculosis

Abstract: We report on 14 patients with tuberculosis of the spine treated by operation. All had disease of three or more vertebrae with involvement of both the anterior and posterior columns and a progressive kyphotic deformity in spite of conservative treatment. We consider such spines to be 'unstable' and have found that anterior as well as posterior fusion with instrumentation is necessary.Résumé Nous rapportons 14 cas de patients atteints de tuberculose rachidienne traitée chirurgicalement. Tous avaient une affectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
6

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 9 publications
1
15
0
6
Order By: Relevance
“…Thus, anterior debridement combined with posterior fusion and fixation was developed [3,10,12,13,[25][26][27], which enables immediate and sufficient stabilization after kyphosis correction. Table 4 summarizes published reports focused on treatment of active spinal tuberculosis with kyphosis of more than 30°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, anterior debridement combined with posterior fusion and fixation was developed [3,10,12,13,[25][26][27], which enables immediate and sufficient stabilization after kyphosis correction. Table 4 summarizes published reports focused on treatment of active spinal tuberculosis with kyphosis of more than 30°.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis of the thoracic and lumbar spine causing gross destruction of the anterior and middle columns often leads to kyphotic deformity [2,3]. Rajasekaran and Shanmugasundaram [4,5] reported that, among children treated conservatively, only 44% experienced improvement of the deformity, while in the remaining patients there was no change (17%) or deterioration (39%); in particular, kyphosis of more than 60°developed in 3-5% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…These cases can only be treated surgically [2,3,28]. There are several surgical techniques: abscess drainage [7,10], anterior strut grafting [12,19], anterior instrumentation [8,27], posterior instrumentation [14,18], combined anterior and posterior stabilisation [6,9] and video-assisted minimally invasive thoracoscopic spinal operations [16].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, abscess drainage and debridement enhance drug treatment [22]; biopsy specimens can be taken efficiently for histopathological diagnosis [10,21]; local instability and disc degeneration are treated by fusion, which prevents pain and the development of deformity [3,10]; decompression is provided in cases with neurological problems [19]; if there is any deformity, it can be corrected [14,18]; surgical treatment leads to rapid recovery and early mobilisation [5,21].…”
Section: Discussionmentioning
confidence: 99%
“…To promote neurological improvement 15 and facilitate early patient ambulation, 16 the spine should be stabilised after debridement and decompression. The curetted interbody cavity is packed with bone grafts after decompression.…”
Section: Discussionmentioning
confidence: 99%